Incidence Trends and Mortality of Giant Cell Arteritis in Southern Norway. Issue 3 (25th February 2021) - Andersen, Jintana B.; Myklebust, Geirmund; Haugeberg, Glenn; Pripp, Are H.; Diamantopoulos, Andreas P.
Abstract : Objective: Southern Norway consists of a homogeneous population of nearly 300, 000 inhabitants and is an ideal epidemiologic setting. We aimed to explore potential changes in incidence of giant cell arteritis (GCA) in Southern Norway from 2000–2013, with comparisons of previous reports from the same population cohort from 1987–1994 and 1992–1996, and to investigate the mortality rates of GCA over a period of 14 years. Methods: All patients diagnosed with GCA during January 1, 2000 to December 31, 2013 were identified through the electronic health records and biopsy findings databases at our clinic. The diagnosis of GCA and information about death was confirmed by reviewing the patients' hospital records. Inclusion criteria were: 1) fulfillment of the American College of Rheumatology 1990 criteria for GCA, or 2) histologically proven GCA, or 3) confirmed arteritis of the large or medium‐sized vessels by imaging. Results: A total of 206 patients were included, and 147 (72%) were females. The annual incidence rate of GCA per 100, 000 inhabitants age ≥50 years was 16.8 (95% confidence interval [95% CI] 14.6–19.2), 24.5 for females (95% CI 19.2–26.5), and 10.2 for males (95% CI 7.9–13.2). Forty‐six patients (22%) died (24 women, 22 men). The overall standardized mortality ratio was 1.05 (95% CI 0.77–1.38), 0.92 for females (95% CI 0.61–1.35), and 1.38 for males (95% CI 0.88–2.05). Overall survival rate was significantly higher in females compared to males ( P < 0.001). Conclusion: GCA incidence is not increasing. We did not find excess mortality; however, males seem to have a worse survival rate compared to females.